Certain Inequalities Involving Generalized Hyperbolic Sine and Cosine Functions - Ghodechor, Sanjay; Darkunde, Nitin (Communications in Mathematics and Applications, 2024)
In this article, we established generalizations of some inequalities involving generalized hyperbolic functions to establish several lower and upper bounds of known inequalities. The implanted results give the sharpness of inequalities.
Keywords: Hyperbolic function; Generalized hyperbolic functions